Tobacco-related cancers in India: A review of incidence reported from population-based cancer registries - Smita Asthana; Rakshit S Patil; Satyanarayana Labani (Indian Journal of Medical and Paediatric Oncology)
Background: Tobacco related cancers (TRC) account for major share of all cancers and updated of incidence data are helpful in policy changes. The aim was to present an update of TRCs on age-adjusted incidence data and corresponding lifetime risk of developing TRC for different regions of the country. Methods: The data for this study were obtained from published reports of 25 population-based cancer registries (PBCRs) in India. The PBCRs in different parts of India were divided into seven regions such as North, South, Central, Northeast, West, Rural West, and East. Data indicators such as age-adjusted rates (AARs) of incidence and the cumulative risks of TRCs up to the age of 64 years for each of the 10 TRC sites of either sex in each of 25 registries were obtained from the National Cancer Registry Programme reports. Results: Among all TRCs, esophagus, lung, hypopharynx, and mouth are the leading sites for both males and females. Males in Northeast region had the highest risk 1 in 27 of developing esophageal cancer, 1 in 67 for cancer of lungs and hypopharynx, followed by 1 in 143 for both mouth and tongue cancers. Females also had the highest risk of esophagus and lungs (1 in 63 female) and cancer of mouth (1 in 250) in Northeast region. Proportion of TRC in comparison of all cancer ranged from 11–25% for men and 3–18% for women. Conclusions: Proportion of TRC in relation to all cancers was still high in different registries of India including the Northeast region.